Urgency of Establishing a National Spices and Herbal Agency In Realizing Golden Indonesia 2045 - Muhammad Haris Zulkarnain; Yaya Sunaryo; Yudi Pratama; Riskal Arief; Asy’ari Muchtar; Irma Suryani Harahap (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Indonesia has a very large potential for